Body, breath & consciousness : a somatics anthology : a collection of articles on family systems, self-psychology, the bodynamics model of somatic developmental psychology, shock trauma, and breathwork - Macnaughton, Ian (Berkeley, CA North Atlantic Books, 2004)
The forces that develop the self—somatic, emotional, mental, interpersonal, social, and spiritual—must all be considered by therapists in treating any patient. Each article in this important anthology deals in some way with these various elements. The writing is focused on the body-mind connection, exploring the practices and theories of this popular branch of psychology. Topics include the significance of family systems; dealing with trauma and shock in therapy; and the importance of breathing, offering valuable insights for the student and practitioner alike. Contributors include Marianne Bentzen, a trainer in Somatic Developmental Psychology; Peter Bernhardt, a professor of psychology; and Peter A. Levine, author of Waking the Tiger.
INTRODUCTION 2
PART ONE: FAMILY SYSTEMS AND THE BODY-MIND 4
Multigenerational Family Therapy 5
-David Freeman, D.S.W.
Expanding the Field of Family Therapy 21
-Ian Macnaughton, Ph.D.
The Narrative of the Body-Mind - Minding the Body 25
-Ian Macnaughton, Ph.D.
PART TWO: BODY-MIND APPROACHES AND SELF-PSYCHOLOGY 36
The Body Self in Psychotherapy 37
-Marianne Bentzen, M.A., Erik Jarlnaes, M.A., Peter Levine, Ph.D.
Sensory Functioning in Psychotherapy 51
-Erving Polster, Ph.D.
The Use of Touch in Psychotherapy: Theoretical and Ethical Considerations 56
-Les Kertay & Susan L. Reviere, Georgia State University
Ethical Consideration in Somatic Therapies 68
-Ian Macnaughton, Ph.D., Marianne Bentzen, M.A., Erik Jarlnaes, M.A.
PART THREE: THE BODYNAMICS MODEL - SOMATIC DEVELOPMENTAL PSYCHOLOGY 75
Individuation, Mutual Connection and the Body's Resources 76
-Peter Bernhardt, M.F.C.C.
The Art of Following Structure - Exploring the Roots of the Bodynamic System 85
-Peter Bernhardt, M.F.C.C.
Waking the Body Ego, Part 1: Core Concepts and Principles 101
-Peter Bernhardt, M.F.C.C., Marianne Bentzen, M.A., Joel Isaacs, Ph.D.
Waking the Body Ego, Part 2: Psychomotor Development and Character Structure 121
-Peter Bernhardt, M.F.C.C., Marianne Bentzen, M.A., Joel Isaacs, Ph.D.
Caring for Yourself While Caring For Others 152
-Merete Holm Brantbjerg
Psychological Muscle Function (diagram) 161
-Bodynamic Institute
PART FOUR: TRAUMA 163
Panic, Biology and Reason: Giving the Body its Due 164
-Peter Levine, Ph.D.
Using the Bodynamic shock trauma model in the everyday practice of physiotherapy 178
-Barbara Picton, BSR, M.Ed. (Cns. Psch.), RCC
It Won't Hurt Forever...Guiding Your Child Through Trauma 191
-Peter Levine, Ph.D., and Maggie Kline, M.S., M.F.T.
Character Structure and Shock 208
-Steen J_rgensen, Cand. Psych.
PART FIVE: BREATHING INTRERVENTIONS 223
The Bioenergy System 223
-Ian Macnaughton, Ph.D.
Breath and Consciousness 229
-Peter Levine, Ph.D. & Ian Macnaughton, Ph.D.

AFTERWORD 248
ABOUT THE EDITOR 249
Includes bibliographical references
Keywords: Mind and body therapies; Psychotherapy; Mind and body